Epic Stone Butch transmasculinity in the work of Willa Cather - Hammer, K. Allison (Transgender Studies Quarterly, 2020)
Through application of the contemporary term transmasculinity and the more historical stone butch, the author questions the critical tendency to perceive American writer Willa Cather only as lesbian while ignoring or undertheorizing a transgender longing at play in her fiction, short stories, and letters. While biographical evidence must not be approached as simply coterminous with literary production, as literature often exceeds or resists such alignments, Cather's letters in particular suggest a strong identification with her male fictional alliances. Analysis of her letters alongside two of her most treasured, and disparaged, novels, One of Ours (1922) and The Professor's House (1925), conveys Cather's wish for an idealized masculinity, both for herself and for Western culture, that would survive two coeval historical processes and events: the closing of the American frontier and the First World War. Through what the author calls a stone butch “armature,” she and her characters retained masculine dignity despite historical foreclosure of Cather's manly ideal, Winston Churchill's Great Man, who was for her the artistic and intellectual casualty of the period. Cather expressed the peculiar nostalgic longing present in stone butch, and in the explosion of new forms of transmasculinity in the present. This suggests that historical transgender styles don't disappear entirely, even as new categories emerge.
Keywords: 1900-1999; 1910-1919; 1920-1929; amériques; approches et analyses; arts; butch; discipline; identités LGBTQIA2+; personnes trans*; périodes historiques; queer; régions géographiques; états-unis; études littéraires

Histoire de l'homosexualité en Europe: Berlin, Londres, Paris, 1919-1939 - Tamagne, Florence (Univers historique, 2000)
Pour l'histoire de l'homosexualité en Europe, l'entre-deux-guerres représente une période cruciale. Comme jamais auparavant, l'homosexualité s'y manifeste au grand jour. Alors que l'Allemagne voit se constituer de véritables mouvements porteurs de revendications politiques qui font de Berlin la capitale de la nouvelle culture, l'Angleterre emprunte le chemin de la subversion de l'ordre victorien, que tandis que la France, malgré une plus grande tolérance, reste sensible à une homosexualité non militante et individualiste. Cette explosion libératrice des mœurs et des mentalités n'aura pourtant pas les retombées sociales et politiques espérées et c'est d'Allemagne que viendra, dans les années trente, le signal de la répression. Celle-ci frappera provisoirement d'un coup d'arrêt une dynamique qui reprendra soufflé dans les années soixante. Reste qu'en quelques années l'homoérotisme trouve une nouvelle légitimation, l'homosexuel devient une figure possible de l'existence sociale. C'est dire l'importance du livre de Florence Tamagne pour comprendre la lente et difficile marche vers la reconnaissance de la communauté homosexuelle et lesbienne.
Keywords: 1900-1999; 1920-1929; 1930-1939; LGBTQIA2+; allemagne; angleterre; approches et analyses; berlin; cours; discipline; europe; france; histoire et politique; identités LGBTQIA2+; londres; militance; paris; premier cycle; périodes historiques; queer; régions géographiques; shm4000; thématiques